First Bistatic Spaceborne SAR Experiments with TanDEM-X - Rodriguez-Cassola, Marc; Prats, Pau; Schulze, Daniel; Tous-Ramon, Nuria; Steinbrecher, Ulrich; Marotti, Luca; Nannini, Matteo; Younis, Marwan; Lopez-Dekker, Paco; Zink, Manfred; Reigber, Andreas; Krieger, Gerhard; et al. (IEEE Geoscience and Remote Sensing Letters, 2012)
TanDEM-X is a high-resolution interferometric mission with the main goal of providing a global and unprecedentedly accurate digital elevation model (DEM) of the Earth surface by means of single-pass X-band SAR interferometry. Despite its usual quasi-monostatic configuration, TanDEM-X is the first genuinely bistatic SAR system in space. During its monostatic commissioning phase, the system has been mainly operated in pursuit monostatic mode. However, some pioneering bistatic SAR experiments with both satellites commanded in non-nominal modes have been conducted with the main purpose of validating the performance of both space and ground segments in very demanding scenarios. In particular, this letter reports about the first bistatic acquisition and the first single-pass interferometric (mono/bistatic) acquisition with TanDEM-X, addressing their innovative aspects and focussing on the analysis of the experimental results. Even in the absence of essential synchronisation and calibration information, bistatic images and interferograms with similar quality to pursuit monostatic have been obtained.
DLR Import::2019-04-02
Keywords: Bistatic radar; bistatic SAR processing; spaceborne SAR missions; synthetic aperture radar (SAR); time and phase synchronization